Penerapan Pupuk Organik Blotong Untuk Meningkatkan Kesuburan Tanah Pada Lahan Tebu di PG. Pradjekan PT. Sinergi Gula Nusantara - Irawan, Triono Bambang; Kusuma, Satria Indra; Aisyah, Anni Nur; Soelaksini, Liliek Dwi; Harlianingtyas, Irma (P3M Politeknik Negeri Jember, 2024)
Sugar factories during the process of milling sugar cane stalks usually produce solid waste in the form of filter cake or filter cake or filter press mud which amounts to around 3.8% of the weight of the sugar cane. The accumulation of large quantities of filter cake is a source of serious environmental pollution for sugar factories and surrounding communities, whereas during the rainy season, piles of wet filter cake emit a foul smell and pollute the environment. On the other hand, filter cake can be used as organic fertilizer. Long-term application of filter cake fertilizer can increase the physical, biological and chemical fertility of degraded land. Application of filter cake organic fertilizer in sugar cane fields at PG Pradjekan PT. Nusantara Sugar Synergy provides benefits, including: minimizing sources of environmental pollution produced by PG. Pradjekan in the form of filter cake waste, utilizing filter cake waste produced from the process of milling sugar cane stalks into organic filter cake fertilizer, accelerating the decomposition process of filter cake by spraying the decomposer to become organic filter cake fertilizer, creating organic filter cake fertilizer from filter cake waste which can be applied to sugar cane land which is useful for increasing Soil organic carbon levels in sugar cane fields and PG Pradjekan PT. Synergy Gula Nusantara is able to produce and apply organic filter cake fertilizer to its sugar cane fields which is carried out when the sugar cane stalks are 2 months to 4 months old.